Utilization of Social Media-Based Learning Videos to Improve Students' Science Literacy in Biology - Nely Sa'adaniyah; Kartika Ratna Pertiwi; Anggi Tias Pratama (Postgraduate, University of Mataram, 2024)
The writing of this article aims to present the results of the analysis in the form of a literature review on the results of research on the utilization of social media-based learning videos to improve students' science literacy. The literature review was conducted on 10 articles published in various journals from 2020 to 2023. The literature review was carried out with 4 steps, namely searching and selecting articles related to the specified topic, analyzing and synthesizing the literature, and organizing the writing. The results of the literature review and analysis show that: 1) the types of research used are development research, experimental research and class action research.2) In general, the use of social media-based learning videos in research has a positive and significant impact on students' science literacy skills.